Construction of Regulations for the Development of Coastal Areas for Tourism based on Local Wisdom in Pandeglang Regency, Banten - Novyana, Hilda; Suherman; Ramadhani, Dwi Aryanti; Muthia Sakti; Erina Nur Afifa (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
In a country, territory is one of the mandatory elements for the establishment of the country. The potential owned by a region will not be utilized optimally if there is no development of the region. This study aims to determine how the construction of regulations in the development of coastal areas by Pandeglang Regency, to determine the effectiveness of the construction of regulations that have been owned by Pandeglang Regency and what problems arise, as well as solutions that can be applied as a solution to these problems. The normative legal research method is carried out by means of a literature study in the form of secondary data as a basic material for research and also by carrying out a qualitative approach. Pandeglang Regency has great potential for the development of coastal tourism. However, to maintain the sustainability of the local environment and culture, regulations are needed that integrate local wisdom in every aspect of tourism development. The results of the study indicate the need for regulations based on local wisdom to ensure sustainable coastal tourism development and provide adequate legal protection for the local community and environment. Keywords: Regulation, tourism, coastal, local.